An Iron‐Decorated Carbon Aerogel for Rechargeable Flow and Flexible Zn–Air Batteries. Issue 32 (1st July 2020) - Wu, Kunze; Zhang, Lei; Yuan, Yifei; Zhong, Linxin; Chen, Zhongxin; Chi, Xiao; Lu, Hao; Chen, Zehong; Zou, Ren; Li, Tingzhen; Jiang, Chengyu; Chen, Yongkang; et al.
Abstract: Mechanically stable and foldable air cathodes with exceptional oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities are key components of wearable metal–air batteries. Herein, a directional freeze‐casting and annealing approach is reported for the construction of a 3D honeycomb nanostructured, N, P‐doped carbon aerogel incorporating in situ grown FeP/Fe2 O3 nanoparticles as the cathode in a flexible Zn–air battery (ZAB). The aqueous rechargeable Zn–air batteries assembled with this carbon aerogel exhibit a remarkable specific capacity of 648 mAh g −1 at a current density of 20 mA cm −2 with a good long‐term durability, outperforming those assembled with commercial Pt/C+RuO2 catalyst. Furthermore, such a foldable carbon aerogel with directional channels can serve as a freestanding air cathode for flexible solid‐state Zn–air batteries without the use of carbon paper/cloth and additives, giving a specific capacity of 676 mAh g −1 and an energy density of 517 Wh kg −1 at 5 mA cm −2 together with good cycling stability. This work offers a new strategy to design and synthesize highly effective bifunctional air cathodes to be applied in electrochemical energy devices. Abstract : The designed strategy of a mechanically integrated air electrode, realized by directional freeze‐casting, generates a 3D honeycomb‐nanostructured Fe‐decorated carbon aerogel with satisfactory mechanical stability and gas/electrolyte diffusion channels. Such an integrated monolith with superb bifunctional electrocatalytic activity shows a remarkable performance as the free‐standing air cathode in a flow Zn–air battery (ZAB) and flexible solid‐state ZAB.